MUHAMMAD THAHIR IBN ‘ÂSYÛR DAN PEMIKIRANNYA TENTANG MAQASID AL-SYARI’AH - Siti Muhtamiroh (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2013)
In the study of of Islamic law, maqâşid al-syarî’ah has a central position. It is because the maqâşid al-syarî’ah does not only imply on the dyamic of Islamic law but also on elasticity of Islam. In discussion on the maqâşid al-syarî’ah, we can’t forget Ibn ‘Âsyûr who has a complete name Muhammad Thahir Ibn ‘Âsyûr. He was the continuing pioneer of maqâşid al-syarî’ah after al-Syathiby. If al-Syathiby was regarded as the founding father of the maqâşid al-syarî’ah, Ibn ‘Âsyûr has developed it into systematized methodology in the Islamic law. Ibn ‘Âsyûr said that the ignorance of the significance of the maqâşid al-syarî’ah in the syari’ah was the leading factor of the fiqh stagnance. Historically, Islam experienced the golden age in the classical periode (750-1250 AD) and it gradually declined in the medieval periode (1250-1800 AD). In the perspective of Islamic law, it was caused by different attention of the maqâşid al-syarî’ah in the each period.